The Ways of School of Business and Management Institut Teknologi Bandung to Colaborate with the Existing Business - Pradana, Johannes Xaeno Satrio; Lantu, Donald Crestoful (Journal of Business and Management, 2016)
Abstract. School of business and Management (SBM ITB) one of the faculty in Institut Teknologi Bandung is a new faculty that aim to produce young entrepreneur and also prepared to be a top level management person in the future. A program already prepared by SBM ITB to help their student started their own business, it's called Integrated Business Experience (IBE). SBM ITB hopes that by having this subject, it could stimulate their student to start being entrepreneur. In fact, almost every company that was build during IBE stop running their business when the subject is finish, but there are also some company that continue their business that find some difficulties to scale their business. The research tries to explore how to create a partnership between an IBE company and SBM ITB that could help the company become sustainable. The study was the guidance of collaborative action research model, which consists of initial reflection, plan, and act. The initial reflection was done to know the problems of the existing businesses, WOODKA and GOODISM Inc. The plan phase was to know what kind of program and solution that can be prepared by SBM ITB to solve the businesses’ problems. Lastly, the act phase was to give recommendations on what thing that can be done together by SBM ITB and the business to solve the current problems. The result of this study shows that the problems revolve around sales, production, funding, internal, and working system. Then, the things that SBM ITB can provide was including sales and networking. Therefore, SBM ITB can introduce its networks to fund the current businesses, giving mentoring about working system and managing internal team, and lastly by the help of CIEL SBM ITB’s program the current businesses can promote their prouct more by joining merchandising store.Keywords: University, Action research, Collaborative action research, Business, Startup